2009
DOI: 10.1002/app.30098
|View full text |Cite
|
Sign up to set email alerts
|

Solid state mechano‐chemical grafting copolymerization of hydroxyethyl cellulose with acrylic acid

Abstract: The effects of mechanochemical treatment on hydroxyethyl cellulose (HEC) and its grafting reaction with acrylic acid (AA) under solvent-free conditions were studied through a vibratory ball-milling machine, which was developed in our laboratory. Fourier transform infrared (FTIR) spectroscopy and 13 C-NMR analysis were used to investigate the structural development of HEC during vibromilling and the grafting mechanism. Further development of the structure and properties of the graft copolymer was characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…Meanwhile, because of the advantages of the ball milling as solvent free, low reaction temperature, low energy consumed and great efficiency, the ball-milling processing should be one of the most suitable methods used on the modification of cellulosic materials (Pucciariello & Bonini, 2008). In our previous work, the grafting copolymerization of hydroxyethyl cellulose with acrylic acid in ball milling was successfully achieved (Chen, Yi, Wu, & Guo, 2009). In this work, the degradation kinetics of HEC during the milling and effecting factors such as milling time, charge ratio of steel ball/HEC, rotational speed on mechanochemical degradation are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, because of the advantages of the ball milling as solvent free, low reaction temperature, low energy consumed and great efficiency, the ball-milling processing should be one of the most suitable methods used on the modification of cellulosic materials (Pucciariello & Bonini, 2008). In our previous work, the grafting copolymerization of hydroxyethyl cellulose with acrylic acid in ball milling was successfully achieved (Chen, Yi, Wu, & Guo, 2009). In this work, the degradation kinetics of HEC during the milling and effecting factors such as milling time, charge ratio of steel ball/HEC, rotational speed on mechanochemical degradation are studied.…”
Section: Introductionmentioning
confidence: 99%
“…Now there have appeared large quantities of literatures concerning of this kind of polymers [23][24][25][26][27][28][29]. After partial hydrophobization, the cellulose derivatives can be dissolved in common organic solvents, which makes the further functionalization much easier and better controlled.…”
Section: Introductionmentioning
confidence: 99%
“…The photostabilizer was prepared through the mechanochemical reaction of PVC with the r‐LS in a vibratory ball‐milling machine developed in our laboratory 16–20. PVC powder (200 g) and 20 g of the r‐LS with various amounts of K 2 S 2 O 8 were added to the jar, which was loaded with steal balls.…”
Section: Methodsmentioning
confidence: 99%
“…It is an effective method for enhancing the compatibility of polymer blends and the interactions between polymers and fillers through stress‐induced chemical reactions between polymers and between polymer and fillers 11–15. Self‐plasticizing aids for PVC and a core–shell impact modifier for PVC have been prepared through mechanochemical degradation and the modification of PVC in our laboratory 16–20. Qiu and coworkers21, 22 found that maleic anhydride could be successfully grafted onto polypropylene by the ball‐milling method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation